2004
DOI: 10.1101/gad.1200804
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular transcription of G-rich DNAs induces formation of G-loops, novel structures containing G4 DNA

Abstract: We show that intracellular transcription of G-rich regions produces novel DNA structures, visible by electron microscopy as large (150-500 bp) loops. These G-loops are formed cotranscriptionally, and they contain G4 DNA on one strand and a stable RNA/DNA hybrid on the other. G-loop formation requires a G-rich nontemplate strand and reflects the unusual stability of the rG/dC base pair. G-loops and G4 DNA form efficiently within plasmid genomes transcribed in vitro or in Escherichia coli. These results establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
490
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 482 publications
(522 citation statements)
references
References 78 publications
25
490
1
Order By: Relevance
“…Persistent R-loops can become deleterious, however. These aberrant R-loops are generally stabilized by the formation of G-quadruplexes in the displaced, G-rich nontemplate strand, which can trigger gene down-regulation or DNA double-strand breaks through as-yet unclear mechanisms (39,41). To date, two distinct mechanisms for R-loop formation in neurodegeneration have been proposed, depending on the genetic insult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persistent R-loops can become deleterious, however. These aberrant R-loops are generally stabilized by the formation of G-quadruplexes in the displaced, G-rich nontemplate strand, which can trigger gene down-regulation or DNA double-strand breaks through as-yet unclear mechanisms (39,41). To date, two distinct mechanisms for R-loop formation in neurodegeneration have been proposed, depending on the genetic insult.…”
Section: Discussionmentioning
confidence: 99%
“…R-loop formation is limited by the rapid association of RNA-binding proteins with the nascent RNA during transcription and splicing, preventing hybridization to the DNA template, and is actively resolved by RNA:DNA helicase activity and RNase H1/H2 activity (39,40). The presence of G-rich nontemplate strands can stabilize R-loops by folding into G-quadruplexes and further contribute to double-strand break formation (39,41). Knockdown of RNA splicing and transport factors has been associated with increased R-loop formation and DNA damage (42,43).…”
Section: Smnmentioning
confidence: 99%
“…(47) However, EM data of these sequences in vitro have been interpreted as suggesting G-quartet formation. (49) Recent examples of well-studied non-B DNA structures, which are pathologically relevant are described below.…”
Section: Lymphoid Translocations: An Overviewmentioning
confidence: 99%
“…Although there is no demonstration yet that the G-quadruplex forms in the cell for human telomeric DNA, recent studies of the telomeres of Stylonychia macronuclei indicated that G-quadruplexes can indeed form in vivo (11), and their formation is controlled by telomere end binding proteins in vivo (12). In addition, intracellular formation of the G-quadruplex was observed in the nontemplate G-rich sequence during transcription (13).…”
mentioning
confidence: 99%